Service Learning and Community Engagement in Graduate Social Work Classrooms: One Student's Perspective - Christina J. Messer Gaitskill (The University of Alabama, 2022)
Appalachian Ohio is a unique community with a rich history, which presents both strengths and challenges for community engagement initiatives. This paper describes a service-learning project that offered cultural diversity training to professionals in Appalachia as a foundational component of a social work program focus on community engagement.